Isokinetic strength and body composition of elite male soccer players during pre-season - (:unkn) unknown (My University, 2004)
Purpose: The purpose of the study was to compare body composition and isokinetic strength of the hamstring and quadriceps muscles at 60°/sec and 180°/sec in healthy subjects and elite male soccer players during the pre-season period. Material and methods: 20 elite soccer players (SP) and 20 university male students (healthy subjects) were included in the study. The subjects were tested for peak torque (PT) (Nm), total work (J), and concentric hamstrings/quadriceps (H:Q) ratio of both knees at 60°/sec and 180°/sec on a Cybex 350 isokinetic dynamometer. Body composition was also assessed by skinfold measurements in the study. Fat-free mass (kg), fat mass (kg) and percentage of body fat were determined according to the Jackson and Pollach equation. Results: The concentric H:Q ratios for the left knee were significantly higher in soccer piayers than in the healthy subjects at angular velocities of 180°/sec (p=0.01). Soccer players had significantly higher fat-free mass, fat mass and percentage of body fat compared to healthy subjects (p<0.05). Conclusion: Based on these findings, we conclude that the mean H:Q ratios of elite soccer players were not in accordance with the literature.
Keywords: Isokinetic, Soccer, Body composition; Muscle strength